PENGARUH STRATEGI CO-BRANDING, BRAND EQUITY TERHADAP PURCHASE INTENTION MELALUI BRAND PREFERENCE - Kurniawan, Arif; Suryoko, Sri; Listyorini, Sari (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
In 2003 Daihatsu doing Co-Branding with Toyota to produce two identical products, namely Daihatsu Xenia and Toyota Avanza. Results of Co-Branding makes Daihatsu got many achievements. Daihatsu Xenia including three best-selling MPV in Indonesia, contributing to the Daihatsu Xenia reach above 56% and the contribution make Daihatsu get ranked the two acquisition of the car market in Indonesia. In 2012 Daihtsu Xenia awarded a top brand. This study aims to determine the effect of co-branding strategies, brand equity toward purchase intention through the Brand Preference. This study is included in the explanatory research. Data collection techniques with accidental sampling method with a sample of 100 analyzes conducted qualitatively and quantitatively. Quantitative analysis using validity, reliability test, crosstab, product moment correlation, simple linear regression, coefficient of determination, multiple regression, t test, and path analysis. The results of this study indicate that the strategy of Co-Branding positive effect on brand equity, co-branding strategy positive effect on Brand Preference, Brand Equity positive effect on Brand Preference, Brand Equity positive effect on Brand Preference and Brand Preference positive effect on Purchase Intention. Based on path analysis get information that to improve the Purchase Intention must be done by increasing the effectiveness of co-branding strategy and followed by efforts to increase the brand equity that is able to increase the Brand Preference. Communicate and provide information about products Daihatsu Xenia is interesting as Co-Brand Product Daihatsu-Toyota and innovation should be done so that consumers want to buy, reuse, do not switch to another brand and make the Daihatsu Xenia first choice when buying a MPV.